2015
DOI: 10.1126/science.aad1171
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional control of tissue formation throughout root development

Abstract: Tissue patterns are dynamically maintained. Continuous formation of plant tissues during postembryonic growth requires asymmetric divisions and the specification of cell lineages. We show that the transcription factors, the BIRDs and SCARECROW, regulate lineage identity, positional signals, patterning, and formative divisions throughout Arabidopsis root growth. These transcription factors are postembryonic determinants of the ground tissue stem cells and their lineage. Upon further activation by the positional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
141
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(147 citation statements)
references
References 32 publications
5
141
1
Order By: Relevance
“…Second, we observed that SCR, JKD, BLJ, and SCZ could function as ground tissue lineage determinants during de novo root organogenesis. The combined action of BLJ, JKD, and SCR is required to maintain the ground tissue lineage postembryonically, and lacking these three factors results in missing ground tissue initializations (hence fewer ground tissue cell rows are observed in cross sections: Moreno-Risueno et al, 2015). We observed that de novo formed roots in blj-1 jkd-4 scr-4 and jkd-4 scz-1 mutants were missing ground tissue cell rows shortly after emergence, which indicates incorrect specification of ground tissue initials during primordia formation or later on in the course of development.…”
Section: Root Primordia Initiation and Patterningmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we observed that SCR, JKD, BLJ, and SCZ could function as ground tissue lineage determinants during de novo root organogenesis. The combined action of BLJ, JKD, and SCR is required to maintain the ground tissue lineage postembryonically, and lacking these three factors results in missing ground tissue initializations (hence fewer ground tissue cell rows are observed in cross sections: Moreno-Risueno et al, 2015). We observed that de novo formed roots in blj-1 jkd-4 scr-4 and jkd-4 scz-1 mutants were missing ground tissue cell rows shortly after emergence, which indicates incorrect specification of ground tissue initials during primordia formation or later on in the course of development.…”
Section: Root Primordia Initiation and Patterningmentioning
confidence: 99%
“…In addition, WUSCHEL-RELATED HO-MEOBOX5 (WOX5) is confined by auxin signaling into the QC and represses differentiation of the stem cell niche, primarily from the QC (Sarkar et al, 2007;Forzani et al, 2014;Pi et al, 2015;Zhang et al, 2015). Tissue formation in the primary root meristem also requires lineage-specific factors that function as cell fate determinants and as tissue endogenous signaling factors to incorporate positional information into patterning (Moreno-Risueno et al, 2015). However, little is known about how tissues are formed de novo.…”
mentioning
confidence: 99%
“…Unlike their animal counterparts, the postembryonic development of higher plants depends on the activity of apical meristems residing at each end of the body Sena et al, 2009;Moreno-Risueno et al, 2015). In the shoot apical meristem (SAM), pluripotent stem cells reside in a specialized microenvironment termed the stem cell niche, which gives rise to the aerial part of the plant (Aichinger et al, 2012;Zhou et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it provides a selective barrier for nutrients and acts as a major storage tissue in many plants (1)(2)(3). In Arabidopsis, an elaborate regulatory network has been established for the asymmetric divisions within the ground tissue that give rise to the two ground tissue cell types in the root: endodermis and cortex (4)(5)(6)(7)(8)(9)(10). This network revolves around the central transcriptional regulator SHORT-ROOT (SHR) that moves from the stele into the ground tissue where it is required in the nucleus to maintain endodermis identity and promote asymmetric division in the daughter cells of the ground tissue stem cells to generate separate endodermis and cortex layers (4)(5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…In Arabidopsis, an elaborate regulatory network has been established for the asymmetric divisions within the ground tissue that give rise to the two ground tissue cell types in the root: endodermis and cortex (4)(5)(6)(7)(8)(9)(10). This network revolves around the central transcriptional regulator SHORT-ROOT (SHR) that moves from the stele into the ground tissue where it is required in the nucleus to maintain endodermis identity and promote asymmetric division in the daughter cells of the ground tissue stem cells to generate separate endodermis and cortex layers (4)(5)(6)(7)(8)(9)(10). The nuclear retention of SHR depends on the activity of SCARECROW (SCR) and the BIRD family of transcription factors that are required to maintain ground tissue identity postembryonically (4,6,(8)(9)(10).…”
mentioning
confidence: 99%